ANALISIS EFEKTIVITAS RETRIBUSI DAERAH SEBAGAI SUMBER PEMBIAYAAN OTONOMI DAERAH (PAD) DI KOTA MAGELANG TAHUN 2017-2021 - Zahro, Nilna Syifa; Lestari, Dian; Manurung, Herlina (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2023)
This research aimed to describe the magnitude of the effectiveness of the remuneration of the region as a source of financing of autonomous areas in the city of Magelang. Analyze the effectiveness of the acceptance of regional remuneration as a source of financing of autonomous areas applied in the city of Magelang. The use of data in this research is secondary data. The study uses quantitative descriptives as a method of data analysis with the calculation of efficiency ratio to analyze target data and realization of remuneration receipt of the region over the last five years, which is taken from the data of the implementation report of the budget PAD Kota Magelang Year 2017-2021. The results of this study show that those that do not reach the level of efficiency are in 2020 only reach 69,7615%, while for the years 2017-2019 and 2021 already effective, that is, in 2017 by 115,128%, in 2018 by 114,931%, in 2019 by 131,217%, and in 2021 by 124,286%. Therefore, the extent to which the rehab of the area as a source of autonomous financing of the region has increased has been sufficiently effective and efficient.